2000
DOI: 10.1038/sj.ijo.0801403
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for excess weight gain in children treated for acute lymphoblastic leukaemia

Abstract: OBJECTIVE: To test whether excess weight gain in patients treated for childhood acute lymphoblastic leukaemia (ALL) was predictable using patient characteristics at diagnosis. DESIGN AND SUBJECTS: Longitudinal study of changes in body mass index (BMI) in all 98 patients treated in Scotland on treatment protocol MRC UKALL-XI who had reached at least 3 y post-diagnosis in ®rst remission. MEASUREMENTS: The in¯uence of the following variables on changes in BMI, expressed as a standard deviation score (SDS), was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 25 publications
4
61
2
Order By: Relevance
“…For the remaining 7 studies, the mean z score was calculated in the following ways: as a weighted average based on subgroup values (n = 5), 29,33,34,37,38 estimated based on median and range (n = 1), 39 or calculated based on the BMI z score at diagnosis and the change in BMI z score from diagnosis to study followup (n = 1). 36 Ten studies explicitly reported the SD/SE of the BMI z score. For the remaining 10 studies, the SD was either calculated as a pooled SD based on subgroup values assuming equal variance (n = 5), 29,33,34,37,38 calculated from the 95% CI (n = 2), 16,27 estimated from median and range (n = 1), 39 obtained directly from study authors (n = 1), 30 or estimated based on the SD at diagnosis and SD for the change in BMI z score from diagnosis to study evaluation (n = 1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the remaining 7 studies, the mean z score was calculated in the following ways: as a weighted average based on subgroup values (n = 5), 29,33,34,37,38 estimated based on median and range (n = 1), 39 or calculated based on the BMI z score at diagnosis and the change in BMI z score from diagnosis to study followup (n = 1). 36 Ten studies explicitly reported the SD/SE of the BMI z score. For the remaining 10 studies, the SD was either calculated as a pooled SD based on subgroup values assuming equal variance (n = 5), 29,33,34,37,38 calculated from the 95% CI (n = 2), 16,27 estimated from median and range (n = 1), 39 obtained directly from study authors (n = 1), 30 or estimated based on the SD at diagnosis and SD for the change in BMI z score from diagnosis to study evaluation (n = 1).…”
Section: Discussionmentioning
confidence: 99%
“…These survivors had completed treatment within 10 years at the time of study evaluation. 8,12,13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Only 2 studies 14,40 examined BMI z score assessed $10 years after the completion of treatment (ie, off treatment $10 years). Because neither study reported SD/SE of the BMI z score, the meta-analysis did not include survivors who were off treatment beyond 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations